9514 1404 393
Answer:
- g(x) = 2|x|
- g(x) = -2|x|
- g(x) = -2|x| -3
- g(x) = -2|x -1| -3
Explanation:
1. Multiplying the function by a constant stretches the graph by that constant. Here, you want a stretch factor of 2, so you have ...
g(x) = 2f(x) = 2|x|
__
2. Negating a function causes its graph to be reflected over the x-axis. That makes your second function look like ...
g(x) = -2|x|
__
3. Subtracting 3 from the function value shifts its location on a graph down by 3 units. Your third function will be ...
g(x) = -2|x| -3
__
4. Subtracting a constant from the x-value causes the graph of the function to be shifted right by that amount. Here you want a right shift of 1 unit, so your function is ...
g(x) = -2|x -1| -3